Impact of casting speed on the temperature field of continuously cast steel billets - Klimes, Lubomir (Materiali in tehnologije, 2013)
In continuous casting, the casting speed is one of the most important parameters that influence the entire process of steel production and its productivity. From the physical point of view, the casting speed affects the temperature field formation along the cast steel blank, e.g., the surface and corner temperatures as well as the solidification of the steel, e.g., the shell thickness, the isosolidus and isoliquidus curves, the metallurgical length and the width of the mushy zone. In order to achieve a particular steel structure, the temperature ranges in particular positions (e.g., due to the straightening), and to minimize the occurrence of defects, it is very important to pay attention to a proper determination of the casting speed. The aim of this paper is to investigate the impact of the casting speed on the temperature field formation of continuously cast steel billets, and on the aforementioned parameters. Three steel grades with various chemical compositions and the originally implemented numerical model of the transient temperature field of continuously cast billets in Zeleziarne Podbrezova in Slovakia were utilized for the analysis. The results proved the significant influence of the casting speed on the temperature field formation and on related parameters. The conclusions may be utilized, e.g., for the determination of the casting speed and for the setup of the caster.
Keywords: kontinuirno ulivanje; continuous casting; hitrost ulivanja; casting speed; solidification; strjevanje; temperature field; temperaturno polje